178k views
11 votes
Solve the equation (3x2)(3x4)=36

2 Answers

1 vote

Answer:


3 {x}^(2) * 3 {x}^(4) = 36 \\ 9 {x}^(6) = 36 \\ {x}^(6) = 4 \\ \boxed{x = \sqrt[6]{4} }

is the right answer.

User Michael Malov
by
6.7k points
7 votes

Answer:

The solution to the equation will be:


x=\sqrt[3]{2},\:x=-\sqrt[3]{2}

or


x = 1.26 ,
x = -1.26

Explanation:

Given the expression


\left(3x^2\right)\left(3x^4\right)=36

simplify


9x^6=36

Divide both sides by 9


(9x^6)/(9)=(36)/(9)


x^6=4


\mathrm{For\:}x^n=f\left(a\right)\mathrm{,\:n\:is\:even,\:the\:solutions\:are\:}x=\sqrt[n]{f\left(a\right)},\:-\sqrt[n]{f\left(a\right)}


x=\sqrt[6]{4},\:x=-\sqrt[6]{4}

solving


x=\sqrt[6]{4}


=\sqrt[6]{2^2}

Apply exponent rule:
\left(a^b\right)^c=a^(bc)


=\sqrt[6]{2^2}=2^{2\cdot (1)/(6)}


=\sqrt[3]{2}


= 1.26

Thus,


x=\sqrt[3]{2} (or
x = 1.26 )

similarly solving


x=-\sqrt[6]{4}


x=-\sqrt[3]{2} or (
x = -1.26)

Therefore, the solution to the equation will be:


x=\sqrt[3]{2},\:x=-\sqrt[3]{2}

or


x = 1.26 ,
x = -1.26

User Mina
by
6.0k points